Farmers’ markets contribution to the resilience of the food systems - Agathe Lucas; Roberta Moruzzo; Giulia Granai (Agricultural and Food Economics)
Abstract To mitigate the impacts of future shocks and achieve its targets, the Food Summit 2021 advocates for a transition toward more resilient Food systems. Alternative food movements, such as Farmers’ Markets (FM), claim to contribute to this transition by offering a different approach to food consumption (Bilali in Food energy secur 8: e00154, 2019). FM are spaces where producers and consumers interact directly, trading locally grown and fresh products (Chiffoleau in Agric 6:1–18, 2016; Marsden in Sociologia Ruralis 40:424–438, 2000). The European Commission defines these short supply chains as “involving a limited number of economic operators, committed to cooperation, local economic development, and close geographical and social relations between producers, processors and consumers” (Regulation (EU) No 1305/2013 of the European Parliament and of the Council of 17 December 2013 on support for rural development by the European Agricultural Fund for Rural Development (EAFRD) and repealing Council Regulation (EC) No 1698/2005, 2013). The present study examines the mechanisms by which FM contribute to the resilience of Food systems. Qualitative data were collected from a FM worldwide, a case study involving nine members of the World Farmers’ Market Coalition (WFMC). Results indicate FM resilience stems from their structure and unique position as niche markets. Also, their adaptive capacities and innovation are fostered by flexible governance structures and strong agency yet can be variable in degree depending on the context. As a source of innovation, FM can inspire policies and inform models for broader resilience in Food systems. Supportive policies and additional contextual research are crucial for creating an enabling environment for FM to thrive within the Food systems, and for scaling up successful emerging innovations to the whole Food systems.